Single-longitudinal-mode Brillouin random fiber laser with high linewidth–compression ratio and laser efficiency based on distributed intrinsic feedback mechanism. (December 2022) - Xu, Lulu; Wang, Yingying; Dai, Shixun; Zhang, Lei; Wu, Duanduan; Shen, Haotuo; Yang, Fan; Xu, Zenghua
Highlights: A tunable single-longitudinal-mode random fiber laser with high linewidth–compression ratio and laser efficiency is achieved. With the assistance of the distributed intrinsic feedback mechanism structure and Brillouin amplification, the maximum linewidth–compression ratio of the fiber laser could be as high as 334. The formation process of linewidth compression and single-longitudinal-mode laser output was theoretically analyzed. The proposed mechanism structure can be applicable to other gain-type lasers to suppress longitudinal modes and further compressing the linewidth of laser. Abstract: A single-longitudinal-mode (SLM) Brillouin random fiber laser with high linewidth–compression ratio and laser efficiency was achieved in this work. With the assistance of the distributed intrinsic feedback mechanism structure (DIFMS) and Brillouin amplification, the maximum linewidth–compression ratio of the fiber laser could be as high as 334 when a broader pump laser with 1 MHz linewidth was used. The formation process of linewidth compression and SLM laser output was also theoretically analyzed. The fiber laser exhibited a high laser efficiency of 21.5% owing to the enhanced Rayleigh scattering fiber (ERSF), which acted as the key element of DIFMS. In addition, the fiber laser with ERSF showed a flexible wavelength tunability from 1535 nm to 1565 nm and a good temporal stability with the maximum power fluctuation of less than 0.3 dB during an hour. These results revealed that the proposed DIFMS applicable to other gain-type lasers as a mechanism structure has great applications in suppressing longitudinal modes and further compressing the linewidth of laser.